Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah, dan Belanja Modal terhadap kemandirian Keuangan Daerah Kota Blitar - Yahya, Muhammad; Diah Widajantie, Tituk (Rifa'Institute, 2023)
An independent region is when the region's own-source revenue is the main source of revenue in financing regional expenditures so that it does not depend on loans to stakeholders, the provincial and central governments. The purpose of this research was to examine and analyze the effect of general allocation funds, local revenue and spending capital on the regional financial independence of Blitar City. The research sample is 10 years old, originating from the Blitar City budget report for the 2012-2021 period. Data analysis techniques using SPSS. The results of the study show that the General Allocation Fund and Capital Expenditure have no effect on Regional Financial Independence, while Regional Original Revenues have an effect on Regional Financial Independence.